The Impact of Ethical Norms of Applied Artificial Intelli-gence on Guizhou College Students’ Personalized Learning Satisfaction - Hong Yang; Jacky Mong Kwan Watt (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the impact of ethical norms in the application of artificial intelligence (AI) on personalized learning satisfaction among college students in Guizhou. The research focuses on how ethical aspects, such as data privacy, algorithmic fairness, and transparency, affect students' experiences with AI-driven educational tools. It underscores the importance of user control, ethics training, and system transparency in building trust and promoting active engagement in AI-powered learning environments. Findings from a sample of 388 college students reveal that when students are informed about the ethical considerations behind AI technologies and have control over their data, they exhibit higher satisfaction with personalized learning experiences. Furthermore, the study highlights that the integration of ethical principles into AI applications leads to a more supportive and trustworthy educational environment, improving overall learning outcomes. This research emphasizes that ethical AI practices are essential for fostering a positive and productive learning experience in the context of higher education.